HUBUNGAN MOBILISASI DINI TERHADAP PENYEMBUHAN LUKA POST OPERASI SECTIO CESARIA - Nurul Aini Siagian; Syafira Nusaibah; Andayani Boang Manalu (Jurnal Penelitian Keperawatan Medik, 2019)
Early mobilization includes factors that can affect the process of wound healing after surgery. Immediate mobilization in stages is very useful for the process of healing wounds and preventing infection and venous thrombosis. The purpose of this study was to determine whether there is a relationship between early mobilization and the process of healing wound post operative sectio caesarea at Sinar Husni General Hospital Medan Helvetia. The research design used was analytic survey with cross sectional approach. The sample in this study used the Consecutive Sampling method of data collection using a checklist sheet conducted on a sample of 19 respondents. The results of the study in this study are the majority of respondents who did early mobilization and who experienced rapid wound healing process as many as 4 people (21%) while the minority of respondents who did early mobilization and who experienced slow wound healing process were 1 person (5.3%). The majority of respondents who did not mobilize early and who experienced a slow wound healing process were 11 people (57.9%) and a minority who did not mobilize early and who experienced rapid healing as many as 4 people (21.1%). Statistical test results obtained p value = 0.046 <0.005. The conclusions of the results of this study indicate there is a relationship between early mobilization and the process of healing post operative sectio of caesarea. Suggestions The results of this study can be applied as a reference to improve nursing care services, especially in providing counseling and assistance to patients.